ANALYSIS OF ABSORPTION CAPACITY OF LIBRARY SCIENCE ALUMNI OF UIN RADEN FATAH PALEMBANG AND ITS RELEVANCE TO THE CURRICULUM - Yanto Yanto; Misroni Misroni (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2020)
Competition in the Global Era, which is currently getting tighter, demands every institution, especially Higher Education Institutions, to be able to produce alumni in accordance with the demands of the times. The orientation of learning outcomes in tertiary institutions is not seen from the scores obtained, but more than that it is expected that alumni who have graduated in tertiary institutions have the ability based on the internalization of knowledge, attitudes, skills, competencies and accumulated work experience. To find out and measure the quality of higher education institutions, one of which is tracing the tracks of alumni (Tracer Study). So that the evaluation of the competencies produced by higher education becomes an important thing to do so that the world of higher education is not separated and too far from the real world of work in society. To answer these challenges and needs, a library science study program based on KKNI was designed, 75% of which leads to practical work in the library to produce professional librarians. Based on the results of surveys and research, data shows that the waiting period for alumni is more than 50% under 6 months, even 27% of them have got a job before graduating. While the level of relevance / suitability of the course with the work of the alumni respondents, 81% answered very well.